Synthesis and electrochemical performance of solid solution of layered nanostructured LiCo₁ˍₓ Niₓ O₂ (х = 0.0, 0.1, ..., 0.9) / Kelimah Elong - Elong, Kelimah (2013)
Layered compounds are being investigated extensively due to their high theoretical specific capacities and relatively good cyclability. Lithium cobalt oxide (LiCoO₂) is an excellent cathode material but expensive and not abundant in nature. LiNiO₂, however, is unstable and do not exhibit good electrochemical properties. Substitution of nickel with cobalt may minimize the cobalt content and may reduce production cost. In this work, layered LiCo₁ˍₓ Niₓ O₂ (х = 0.0, 0.1, ...,0.9) via a novel self-propagating combustion synthesis and its electrochemical properties are investigated. Simultaneous Thermogravimetric Analysis (STA), X-Ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X-Ray Spectroscopy and High Resolution Transmission Electron Microscopy (HRTEM) were used to characterize all the materials. The characterization of all samples shows pure and single phase layered hexagonal structured materials obtained at 700 °C for 24 h with a polyhedral like morphology…